Konsep Pendidikan Karakter Keagamaan Untuk Calon Akuntan: Studi Kasus di Program Studi Akuntansi Universitas Muhammadiyah Yogyakarta - Juanda Juanda; Hafiez Sofyani (Universitas Muhammadiyah Yogyakarta, Indonesia, 2016)
This paper describes the concept of religious character education organize for students in Accounting (prospective accountant) at the Universitas Muhammadiyah Yogyakarta (UMY). The program is named Pendampingan Agama Islam (PAI). This paper explain the weaknesses and suggest improvements to the concept of PAI which has been run previously in UMY. This paper also presents various aspects of religious character education in Islamic perspective, such as: the design stage of activities, material formulation and execution model of the program. This paper is expected contributing in the formulation of the concept of education that is based on Islamic values, typically in the university environment, and as a reference literature for the development of educational studies of religious character, especially to the prospective accountant.